PENGARUH GAME EDUKASI WORDWALL TERHADAP KEMAMPUAN PROBLEM SOLVING ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 1 KOTA JAMBI - Aura Salsabila; Indryani; Asih Nur Ismiatun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early childhood problem-solving ability is an important aspect of cognitive development; however, it has not yet developed optimally among children aged 4–5 years at TK Negeri Pembina 1 Kota Jambi. This study aims to determine the effect of using the Wordwall educational game on children’s problem-solving ability. The study employed a quantitative approach with a pre-experimental one group pretest-posttest design. The subjects consisted of 11 children selected through purposive sampling. Data were collected through observation, interviews, and documentation, while data analysis was conducted using the Wilcoxon Signed-Rank Test. The results showed an improvement in problem-solving ability, indicated by an increase in the mean score from 28.18 to 37.63 and a significance value of 0.003 < 0.05. The N-Gain score of 0.60 was categorized as moderate. Therefore, the use of Wordwall has a significant and moderately effective impact on improving early childhood problem-solving ability.